2017
DOI: 10.1111/trf.14012
|View full text |Cite
|
Sign up to set email alerts
|

A national review of the clinical use of group O D– red blood cell units

Abstract: The data appear broadly representative of the current transfusion and inventory management practices surrounding the use of group O D- RBC units. Strategies to reduce O D RBC demand include reevaluation of inventory holdings particularly at smaller centers, increasing the panel of phenotyped RBC units across all ABO groups, more regular rotation of units between hospitals to minimize time expiry, and continuing education for promoting transfusion of ABO-identical RBC units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
36
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 9 publications
2
36
2
Order By: Relevance
“…This result was significant as 24.5% of all O negative PRBC units are transfused after 35–42 days of storage in Australia. 34 These results align with the findings of in vitro studies and support the shortening of PRBC shelf life to 35 days, which has already occurred in some jurisdictions (The Netherlands, UK, Germany, China). Shortening PRBC shelf life should be approached with caution due to its implications for blood bank management, product wastage and PRBC access in remote locations.…”
Section: Discussionsupporting
confidence: 86%
“…This result was significant as 24.5% of all O negative PRBC units are transfused after 35–42 days of storage in Australia. 34 These results align with the findings of in vitro studies and support the shortening of PRBC shelf life to 35 days, which has already occurred in some jurisdictions (The Netherlands, UK, Germany, China). Shortening PRBC shelf life should be approached with caution due to its implications for blood bank management, product wastage and PRBC access in remote locations.…”
Section: Discussionsupporting
confidence: 86%
“…Therefore, in order to understand the absolute requirements for this product in the Australian context, a national survey was conducted to investigate how often group O D− RBC units are used in emergency situations, for neonatal transfusions and obstetric purposes, and for providing phenotypically matched units. The aggregated national data on the findings from this study have recently been published .…”
Section: Introductionsupporting
confidence: 71%
“…As patient blood management becomes more widespread, there has been an international decline in the demand for RBC products . Hirani et al reported that there had been a 21% reduction in demand between 2012 and 2015 in Australia. In contrast, the demand for the “universal” blood group O is, in fact, proportionally increasing .…”
Section: Discussionmentioning
confidence: 99%